Interleukin-1 alpha modulates neutrophil recruitment in chronic inflammation induced by hydrocarbon oil() - Lee, Pui Y. (2010)
Exposure to naturally-occurring hydrocarbon oils is associated with the development of chronic inflammation and a wide spectrum of pathological findings in humans and animal models. The mechanism underlying the unremitting inflammatory response to hydrocarbons remains largely unclear. The medium-length alkane 2,6,10,14 tetramethylpentadecane (TMPD; also known as pristane) is a hydrocarbon that potently elicits chronic peritonitis characterized by persistent infiltration of neutrophils and monocytes. In this study, we reveal the essential role of interleukin (IL)-1α in sustaining the chronic recruitment of neutrophils following TMPD treatment. IL-1α and IL-1 receptor signaling promote the migration of neutrophils to the peritoneal cavity in a CXC chemokine receptor-2 (CXCR2)-dependent manner. This mechanism is at least partially dependent on the production of the neutrophil chemoattractant CXCL5. Moreover, although chronic infiltration of inflammatory monocytes is dependent on a different pathway requiring Toll-like receptor (TLR)-7, type-I interferon receptor, and CC-chemokine receptor-2 (CCR2), the adaptor molecules MyD88, IRAK-4, IRAK1 and IRAK2 are shared in regulating the recruitment of both monocytes and neutrophils. Taken together, our findings uncover an IL-1α-dependent mechanism of neutrophil recruitment in hydrocarbon-induced peritonitis and illustrate the interactions of innate immune pathways in chronic inflammation.